Preparation of glucopyranosylamines in the pipeline reactor - Wang, Shuai; Qian, Chao; Liu, Zhen-Xing; Chen, Xin-Zhi (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2009)
Three kinds of glucopyranosylamines-N-(2-hydroxyethyl)-D-Glucopyranosylamine, N-butyl- beta -D-Gluco-pyranosylamine, and N-cyclohexyl- beta -D-Glucopyranosylamine were synthesized by using D-glucose and organic amines as raw materials in the pipeline reactor, and their yields were 94.3%, 98.1% and 95.7%, respectively. Moreover, with high purity and good color, the structure of the product was characterized by ESI-MS, IR and 1H-NMR. In addition, the synthesis of N-(2-hydroxyethyl)- beta -D-Glucopyranosylamine was mainly studied, the optimized conditions were: methanol/water solution as solvent, molar ratio of ethanolamine to D-glucose in 1.1, 70 degree C, and pressure of 1.0~2.0 MPa.